Atrial fibrillation in patients with Graves disease: incidence, risk factors and outcomes. (3rd October 2022) - Naser, J; Pislaru, S V; Stan, M N; Lin, G
Abstract: Background: Graves' disease (GD) is associated with atrial fibrillation (AF) with a prevalence ranging between 16% and 60%, but its risk factors are not well-defined. We aimed to describe the incidence, risk factors and outcomes of GD-related AF. Methods: Patients diagnosed with GD between 2009 and 2019 were included retrospectively. We defined GD-related AF as AF diagnosed within 30 days before or any time after diagnosis of GD. Late onset AF was defined as GD-related AF diagnosed more than 90 days after GD diagnosis. Observed AF events were compared to the expected events in the general population utilizing published data of age and sex-specific rates of AF. Results: Of 1371 patients with GD, AF occurred in 139 (10.1%) patients. Late onset AF occurred in 32 (23%), of which 50% had attained euthyroidism. The observed incidence of AF was higher in GD than that expected in the general population (p<0.001), Figure 1. When comparing the incidence of only late AF to that in the general population, late AF still happened more frequently in GD although not achieving statistical significance (p=0.06), Figure 1. Independent risk factors were age [HR 1.05 (1.03–1.06) per year], overt hyperthyroidism [HR 2.71 (1.35–5.44)], and male gender [HR 2.42 (1.57–3.71)] for early AF and age [HR 1.06 (1.02–1.09) per year], BMI [1.07 (1.01–1.12) per unit], COPD [3.33 (1.08–10.27)), heart failure [HR 4.19 (1.39–17.42)], and treatment with thionamide [vs. radioiodine ablation HR 2.94 (1.38–6.27)] for late AF. AF was associated with higher rates of mortality [HR 16.32 (4.66–56.58)], acute coronary syndrome/stable angina events [HR 3.89 (1.23–12.31)], and cardiac hospitalizations [HR 15.39 (8.17–29.00)] when adjusted to age, sex, and previous AF. Conclusion: AF occurred in 10.1% of GD patients. Late onset AF is an important entity comprising a quarter of GD-related AF cases and requires surveillance even after restoring euthyroidism. Risk factors for AF in GD are similar to those in general population, although overt hyperthyroidism conferred the highest risk, especially for early AF. Treatment with thionamide was associated with late AF. Funding Acknowledgement: Type of funding sources: None.